Impact of Hydroelectric Power Plant Construction on Water Quality and Socio-Economics in Kerinci Regency - Randa, Agusri; Anis Tatik Maryani; Rosyani, Rosyani (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: The construction of Hydroelectric Power Plant (PLTA) in Kerinci Regency is part of the fulfillment of renewable energy needs that offer clean and sustainable energy solutions, but the impact on the environment and society needs to be assessed in terms of water quality, economy and society around the project.y. Objective: This study aims to conduct a study related to the impact of hydroelectric power plant construction on water quality and socio-economics in Kerinci Regency. Method: descriptive quantitative approach with primary data from water quality measurements and community surveys. The water parameters tested include TSS, temperature, pH, DO, COD, BOD, and turbidity. Socio-economic analysis was conducted through questionnaires to 30 respondents, and statistical tests using Wilcoxon to determine significant differences before and after the construction of the PLTA. Result and Discussion: All water quality parameters meet class II quality standards, some even meet class I. The DO value is also above the minimum limit, indicating that the quality of dissolved oxygen remains good. From the socio-economic aspect, there was a significant change in the number of farmers and entrepreneurs decreased, while the number of employees increased drastically. Community income also increased significantly from before to after construction, and the results of the Wilcoxon test showed a significant difference (p <0.05). Conclusion: the construction of the hydroelectric power plant does not reduce water quality because all parameters are still within the established quality standards and has a significant positive socio-economic impact.